2009
DOI: 10.2337/dc08-1406
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Neural Impairment in Subjects With Impaired Glucose Tolerance

Abstract: OBJECTIVE -To evaluate neural dysfunction in subjects with impaired glucose tolerance (IGT).RESEARCH DESIGN AND METHODS -For this study, 46 subjects with IGT and 45 healthy volunteers underwent detailed neurological assessment. Cardiovascular autonomic function was assessed by standard cardiovascular reflex tests, and heart rate variability was characterized by the triangle index. Sensory nerve function was assessed using Neurometer (for current perception threshold) and Medoc devices. Peak plantar pressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 11 publications
(8 reference statements)
5
46
0
Order By: Relevance
“…Its prevalence varies between 7 and 65% depending on the diagnostic criteria and the studied population increasing with age and DM duration [1]. Moreover, it may be present in newly diagnosed patients with type 1 and type 2 DM and in patients with impaired glucose tolerance [2]. A meta-analysis of 15 longitudinal studies with a follow-up of 1-16 years showed that the definite diagnosis of CAN based on at least 2 abnormal test results is accompanied by a relative risk of mortality of 3.65 [3].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Its prevalence varies between 7 and 65% depending on the diagnostic criteria and the studied population increasing with age and DM duration [1]. Moreover, it may be present in newly diagnosed patients with type 1 and type 2 DM and in patients with impaired glucose tolerance [2]. A meta-analysis of 15 longitudinal studies with a follow-up of 1-16 years showed that the definite diagnosis of CAN based on at least 2 abnormal test results is accompanied by a relative risk of mortality of 3.65 [3].…”
Section: Abbreviationsmentioning
confidence: 99%
“…8 In contrast, another study examined patients with newly diagnosed IGT with a battery of autonomic tests including heart rate variation variability, heart rate response to deep breathing, heart rate response to Valsalva maneuver, blood pressure response to standing up quickly, and skin sympathetic skin response (SSR) that evaluates postganglionic sympathetic sudomotor function but is less precise than the QSART. 7 They found no difference compared to controls in measures of CAN.…”
Section: Statistical Design Analysis Was Performed Using Spss Versionmentioning
confidence: 99%
“…1,2 The neuropathy associated with IGR and early diabetes is a small-fiber neuropathy that is often accompanied by mild autonomic symptoms and abnormalities. [3][4][5][6][7][8] A recent consensus statement by the American Diabetes Association recognizes that glycemic burden is a strong predictor of adverse outcomes and that IGR represents a continuum of risk. 9 Thus, for the purposes of this study, subjects with neuropathy and prediabetes or newly diagnosed diabetes are described as having IGR or early diabetic neuropathy.…”
mentioning
confidence: 99%
“…The diagnosis of neuropathy in IGT is based on careful clinical examination [2,16]. As in diabetes, this should include both motor and sensory modalities, both small- and large-fiber function tests.…”
Section: Peripheral Neuropathy In Igt: How To Diagnosementioning
confidence: 99%